2019
DOI: 10.1111/sode.12390
|View full text |Cite
|
Sign up to set email alerts
|

Equality, equity, or inequality duplication? How preschoolers distribute necessary and luxury resources between rich and poor others

Abstract: The present study investigated preschoolers' multiple sociomoral considerations (equality, equity, and perpetuating inequality) in a third‐party context of social inequality. Using a resource allocation task involving one wealthy and one poor character, we examined how 3–5‐year‐old children (N = 100) allocated either necessary (must‐have) or luxury (nice‐to‐have) resources. In addition, preschoolers' emotions, reasoning, and judgments were assessed. Results indicated that preschoolers distributing more resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
3
32
2
Order By: Relevance
“…The findings of the current study suggest that perhaps participants chose to behave fairly by giving an equal amount of resources to their recipient, regardless of the recipient's financial privilege status, rather than rectifying inequality. This finding is inconsistent with developmental research that suggests children as young as 7 years old reliably rectify inequality on third-party resource allocation tasks (Essler, Lepach, Petermann, & Paulus, 2019;Olson, Dweck, Spelke, and Banaji, 2011). There are two main differences between the methods of the cited developmental research and the current study.…”
Section: Overall Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of the current study suggest that perhaps participants chose to behave fairly by giving an equal amount of resources to their recipient, regardless of the recipient's financial privilege status, rather than rectifying inequality. This finding is inconsistent with developmental research that suggests children as young as 7 years old reliably rectify inequality on third-party resource allocation tasks (Essler, Lepach, Petermann, & Paulus, 2019;Olson, Dweck, Spelke, and Banaji, 2011). There are two main differences between the methods of the cited developmental research and the current study.…”
Section: Overall Findingscontrasting
confidence: 99%
“…Children ages 7 years and older reliably allocated more cookies to the recipient who started with fewer cookies, rectifying the inequality. In a follow-up study, researchers conducted a similar third-party allocation task in which children were asked to allocate either necessary ("need-to-have") resources or luxury ("nice-tohave") resources (Essler, Lepach, Petermann, & Paulus, 2019). Some preschoolers, but not all, rectified the inequalities on this task and were more likely to rectify the inequality for necessary resources (β = −0.367, t(91) = −3.40, p < 0.001).…”
mentioning
confidence: 99%
“…Younger preschoolers of about 3 years of age do not seem to have such a strong consideration for the well‐being of the recipients in resource allocation tasks. Interestingly, some studies have even shown that they favor advantaged over disadvantaged recipients in their moral responding, for example, in their resource allocations (Essler, Lepach, Petermann, & Paulus, 2020; Kenward, Hellmer, Söderström Winter, & Eriksson, 2015; Li, Spitzer, & Olson, 2014). Moreover, 6‐ to 8‐year‐olds but not 3‐ to 5‐year‐olds have been shown to allocate luxury (nice to have) but not necessary (needed to avoid harm) resources more meritoriously and referenced others’ welfare only in their justifications for the allocations of necessary resources (Rizzo et al, 2016).…”
Section: Ownership and Resource Redistributionmentioning
confidence: 99%
“…However, children rectify pre-existing inequalities not only by the amount of resources but also by the value of resources (Blake & Rand, 2010;Essler et al, 2019;Shaw & Olson, 2013;Sheskin et al, 2016;Zhao et al, 2019).…”
Section: Rectifying Inequality Using Resources Of Different Values | 643mentioning
confidence: 99%
“…However, children rectify pre‐existing inequalities not only by the amount of resources but also by the value of resources (Blake & Rand, 2010; Essler et al., 2019; Shaw & Olson, 2013; Sheskin et al., 2016; Zhao et al., 2019). As a type of allocation that develops later than quantitative fairness (Sheskin et al., 2016; Zhao et al., 2019), qualitative fairness places less importance on children's moral reputation because it requires additional investment to determine that a person has taken a quality advantage, as everyone has different value judgments, and it is harder to identify a violation of qualitative fairness (Sheskin et al., 2016).…”
Section: Introductionmentioning
confidence: 99%